Aulas virtuales como herramientas de apoyo en el aprendizaje de los estudiantes de la escuela de educación técnica de la Facultad de Ciencias de la Educación, Humanas y Tecnologías de la UNACH, período 2013 - 2014 - Pinto Guevara, Gonzalo Ernesto (2016)
The thesis presented below is the result of research conducted at the School of Technical Education of the Faculty of Education Sciences, Humanities and Technology UNACH during the academic year 2013 - 2014, on the grounds that there an educational culture regarding the use of virtual classrooms as tools to support the learning of students, gathering information for the purpose aimed to demonstrate the importance of virtual classrooms as an essential openness to the use of information technology and communication (ICT). Deductive, inductive and analytical methods allowed scientists to determine the cause and effect of the problem, performing a field survey through the survey technique which yielded better results and thus test the hypothesis, that is that virtual classrooms as tools support positive impact on student learning. This research involved the collaboration of students and teachers of the school of technical education who made evident the problem is that virtual classrooms despite being a support tool in students' learning, is not a remedy used to supplement of class attendance as well they affirm 43% of students. In this situation an alternative solution to the problem in order to sensitize the educational group on the importance of virtual classrooms as tools to support the learning of students, preparing for such purpose a procedure manual for proper use of the classrooms was proposed virtual at the National University of Chimborazo.